NAVIGATING BODY SHAMING: CHALLENGES AND LESSONS FROM THE EXPERIENCES OF FEMALE UNIVERSITY UNDERGRADUATES IN NIGERIA - FEMI-ADERINTO, ADEDOLAPO MODUPE (Sokoto Educational Review, 2025)
Body shaming is a widespread problem with serious repercussions, and this study investigated its impact on female undergraduates at Obafemi Awolowo University (OAU) in Nigeria. Using a qualitative, descriptive case study design, researchers conducted semi-structured interviews with 12 undergraduates to explore the forms of body shaming they experienced, the contexts in which it occurred, and its effects on their well-being. Thematic analysis of their lived experiences revealed that body shaming instances, perpetrated by people in various contexts, significantly impacted different dimensions of the students’ well-being. In response, participants developed several coping strategies, including practicing self-love and acceptance, seeking support, trivializing mockery, and engaging in education and sensitization efforts. These informal, experiential, and transformative learning processes helped them build personal agency and adaptive skills. The study concludes that unmanaged body shaming can have long-term effects, emphasizing the need for intensified support groups and awareness campaigns to help students combat and cope with this issue. DOI: https://doie.org/10.10318/SER.2025934985